SEQUENCE STRATIGRAPHY ANALYSIS AND POROSITY DELINEATION OF CD CARBONATE UNIT AT KETAPANG AREA, MADURA NORTHERN OFFSHORE, NORTH EAST JAVA BASIN - KRISHNA PRATAMA, RIZKI
BT field is one of the discovery in the Ketapang area that was discovered in the 2000s. Hydrocarbon test result from several wells within the field ranges from 2000 to 3000 BOPD from CD Carbonate unit. In 2010s, hydrocarbon was discovered at BTS prospect with BTS-1 well test result ranges from 400 to 600 BOPD from the same Carbonate unit. The discrepencies of the test result incurred queries on the similarity between BT field and BTS prospect. Sequence stratigraphy analysis is expected to be able to understand the carbonate development of CD Carbonate unit within the research area.